Impact of Tillage, Residue and Nutrient on Soil Active Carbon, Nitrogen and Crop Yields in a Soybean-Wheat Rotation in Vertisols of Central India - Radha Raghuwansi,; Somasundaram Jayaraman,; Abhay Shirale,; Subash C. Gupta,; Nishant K. Sinha,; Kuntal M. Hati,; Bharat P. Meena,; K. Ramesh,; Ashok K. Patra,; Ram C. Dalal, (Journal of the Indian Society of Soil Science, 2024)
This study was conducted as part of an on-going conservation agriculture experiment at ICAR-Indian Institute of Soil Science, Bhopal, which began in 2015. The experiment consists of different tillage system (NT: No tillage, RT: Reduced tillage and CT: conventional tillage), residue retention (30 and 60 cm residue retention) and nutrient doses (75 and 100% recommended dose of fertilizer (RDF), and soil test crop response (STCR dose) in a soybean-wheat sequence. The results showed that tillage, residue retention and nutrient management did not have any influence on soil pH and electrical conductivity (EC). However, there was an improvement in soil organic carbon (SOC) due to RT with 60 cm residue retention, showing an increase of 0.84 per cent after the harvest of wheat. Active carbon (C) improved to 835.7 and 780.6 mg C kg-1 under RT with 60 cm residue retention compared to CT. Both NT (30 and 60 cm residue retention) and RT (30 cm residue retention) also showed higher values of active C compared to conventional tillage (CT) and nutrient management. Ammoniacal (NH4 +-N) and nitrate (NO3--N) nitrogen also behaved in similar fashion under all the treatments. However, the grain, straw and biological yields of wheat crops were significantly higher under CT and STCR but not under soybean crop. Tillage-nutrient interaction was non-significant in improving the crop yields. Therefore, it can be inferred that the CA practice involving RT or NT along with 60 cm residue retention can be adopted to enhance C sequestration and soil health in the context of climate change.